The role of parents' patterns and entrepreneurship learning achievements to grow the interest of entrepreneurs - Arif Hidayat; Rabiman Rabiman; Samsul Hadi (Jurnal Taman Vokasi, 2019)
The aims of this study were to find out: (1) the relationship between parenting and entrepreneurial learning achievement on the interest in entrepreneurship, (2) the relationship between parenting interest in entrepreneurship interests, and (3) the relationship between entrepreneurship learning achievement and entrepreneurial interest. This study included the type of ex-post facto research. The data collection techniques were questionnaires and documentation. The data analysis technique used descriptive analysis, the first hypothesis test used multiple regression and the second and third hypothesis tests used a partial correlation test which was preceded by a test of normality, linearity and independence. The results showed that: (1) There was a positive and significant relationship between parenting and entrepreneurial learning achievement with entrepreneurial interests with a value of R = 0.415 and Freg value = 13.334 with a significance value of 0.000 < 0.05. (2) There was a positive and significant relationship between parenting and entrepreneurial interests with a calculated coefficient r count = 0.312 with a significant level of 0.000 <0.05. There was a positive and significant relationship between entrepreneurial learning achievement and entrepreneurial interest with the coefficient of r count = 0.294 with a significance level of 0.001 < 0.05.